Peningkatan Kompetensi Kewirausahaan Guru dan Siswa SMKN 4 Denpasar Melalui Pelatihan Business Model Canvas - I G A Krisna Lestari; Ni Ketut Bintang Winantari Ningsih; Pande Putu Juniarta (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2024)
The rapid era of technology plays an important role in driving new entrepreneurship. The aim of the community service activity to be conducted is to foster an entrepreneurial spirit and increase knowledge about the business model canvas, design thinking, business plan proposal, digital marketing, and marketplace. The community service activity will be held at SMKN 4 Denpasar. The participants are students of SMKN 4 Denpasar. The problem faced by the school is the lack of training activities related to entrepreneurship. The solution offered to the partners is to provide training to build an entrepreneurial spirit. The method used in this community service activity includes socialization or counseling, discussion, simulation, and application. The results of the community service activities that have been carried out are that the students of SMKN 4 Denpasar have knowledge and are able to create business concepts through the business model canvas, design thinking, business plan proposal, digital marketing, and marketplace.